Employee Turnover: A Meta-Analysis and Review with Implications for Research - Cotton, John L.; Tuttle, Jeffrey M. (Academy of Management Review, 1986)
Studies of employee turnover are reviewed using meta-analytic techniques. The findings indicate that almost all of the 26 variables studied relate to turnover. The findings also indicate that study variables including population, nationality, and industry moderate relationships between many of the variables and turnover. It is suggested that future research on employee turnover: (1) report study variables, (2) continue model testing rather than simply correlating variables with turnover, and (3) incorporate study variables into future models.